2014
DOI: 10.1159/000358064
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of Transforming Growth Factor Beta-1 in Cancer Tissue Predicts a Poor Prognosis for Patients with Stage III Rectal Cancers

Abstract: Objective: Transforming growth factor beta (TGF-β) plays an important role in tumorigenesis and metastasis. It works as a tumor suppressor in the normal colon, but acts as a cancer promoter during the late stages of colorectal carcinogenesis. High expression of TGF-β is known to be associated with advanced stages, tumor recurrence and decreased survival of patients. We investigated the expression of TGF-β and its signaling axis molecules and evaluated their prognostic significance in patients with stage III re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Using IHC study, Lampropoulos et al reported that there was an association of cancer-specific OS with high TGF-b, as well as low SMAD4, and pSMAD2/3 expression in 195 unrelated CRC specimens [33]. Conversely, Chun et al found contrary results regarding the prognostic role of SMAD protein [34]. The loss of SMAD4 protein expression was associated with a reduction in DFS [34].…”
Section: Discussionmentioning
confidence: 99%
“…Using IHC study, Lampropoulos et al reported that there was an association of cancer-specific OS with high TGF-b, as well as low SMAD4, and pSMAD2/3 expression in 195 unrelated CRC specimens [33]. Conversely, Chun et al found contrary results regarding the prognostic role of SMAD protein [34]. The loss of SMAD4 protein expression was associated with a reduction in DFS [34].…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies were conducted in European countries (UK, Germany, Italy, Sweden, Poland, Greece and Bulgaria) and in the United States (US), and four were conducted in Asian countries (China, Japan and Korea) [21, 22, 25, 26]. All the eligible studies were published between 1995 and 2015.…”
Section: Resultsmentioning
confidence: 99%
“…All patients included in the eligible studies underwent surgical resection. Only one study investigated rectal cancer [22], and two investigated colon cancer [25, 27], whereas other studies investigated colorectal cancer. One study included stage III patients [22], and one study included stage I-III patients [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations